Про субоксидну форму кисню в сталях та чавунах - Іванов, В.Г.; Пирожкова, В.П.; Луньов, В.В. (Physico-technological Institute of Metals and Alloys, 2023)
The chemical compounds of oxygen in cast irons and steels with the involvement of petrographic, X-ray- spectral and other methods of analysis have been studied. It has been established that oxygen forms not only super oxides but also suboxides (AlO, Al2O, SiO, Mg2O, etc.) in steels and cast irons. The presence of a suboxide oxygen form in cast irons is of great importance not only in terms of determining the total oxygen content, but more importantly in the formation of the morphology of graphite inclusions and the metal structure.